Finite-time adaptive modified function projective multi-lag generalized compound synchronization for multiple uncertain chaotic systems - Li, Qiaoping; Liu, Sanyang; Chen, Yonggang (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, for multiple different chaotic systems with fully unknown parameters, a novel synchronization scheme called ?modified function projective multi-lag generalized compound synchronization? is put forward. As an advantage of the new method, not only the addition and subtraction, but also the multiplication of multiple chaotic systems are taken into consideration. This makes the signal hidden channels more abundant and the signal hidden methods more flexible. By virtue of finite-time stability theory and an adaptive control technique, a finite-time adaptive control scheme is established to realize the finite-time synchronization and to properly evaluate the unknown parameters. A detailed theoretical derivation and a specific numerical simulation demonstrate the feasibility and validity of the advanced scheme.
Keywords: finite-time adaptive control; modified function projective multiple-lag generalized compound synchronization; unknown parameter; chaotic systems